The Value of Repetitive Transcranial Magnetic Stimulation (rTMS) for the Treatment of Anxiety Disorders: An Integrative Review - Paes, Flavia; Machado, Sergio; Arias-Carrion, Oscar; Velasques, Bruna; Teixeira, Silmar; Budde, Henning; Cagy, Mauricio; Piedade, Roberto; Ribeiro, Pedro; P. Huston, Joseph; T. Sack, Alexander; E. Nardi, Antonio (CNS & Neurological Disorders - Drug Targets, 2011)
Unlike for depression, only few studies are available today investigating the therapeutic effects of repetitive transcranial magnetic stimulation (rTMS) for anxiety disorders. This review aims to provide information on the current research approaches and main findings regarding the therapeutic use of rTMS in the context of various anxiety disorders. Although positive results have frequently been reported in both open and randomized controlled studies, our review of all identified studies indicates that at present no conclusive evidence of the efficacy of rTMS for the treatment for anxiety disorders is provided. Several treatment parameters have been used, making the interpretation of the results difficult. Moreover, sham-controlled research has often been unable to distinguish between response to rTMS and sham treatment. However, there is a limitation in the rTMS methods that likely impacts only the superficial cortical layers. It is not possible to directly stimulate more distant cortical areas, and also subcortical areas, relevant to the pathogenesis of anxiety disorders, though such effects in subcortical areas are thought to be indirect, via trans-synaptic connections. We thus recommend further studies to clearly determine the role of rTMS in the treatment of anxiety disorders. Key advances in combining TMS with neuroimaging technology may aid in such future developments.
Keywords: DLPFC